High temperature erosive wear of a boiler tube steel - Suckling, Martin Brian (Centre for Materials Engineering, 2016)
This work is an attempt to evaluate the influence of critical operational parameters on the high temperature erosion of a 1Cr½Mo boiler tube steel. Erosion testing has been carried out in a specially designed and developed unique laboratory apparatus capable of simulating the conditions of temperature, particle velocity and flux as found in the economiser region of pulverised fuel boiler combustors in electricity generation power plants. The work has encompassed the effects of particle type, size, velocity and flux on the erosive wear rates of the 1Cr½Mo boiler tube steel at temperatures of up to 600°C. The response of the target to impacting erodent particles has been analysed using scanning electron and optical microscopy, transmission electron microscopy (TEM) as well as conducting cross-sectional microhardness tests. The change in the mechanical properties of the steel was determined by conducting tensile tests over a range of temperatures from 20°C to 565°C.